Reactive astrocytes as treatment targets in Alzheimer's disease—Systematic review of studies using the APPswePS1dE9 mouse model. Issue 8 (25th February 2021) - Smit, Tamar; Deshayes, Natasja A. C.; Borchelt, David R.; Kamphuis, Willem; Middeldorp, Jinte; Hol, Elly M.
Abstract: Astrocytes regulate synaptic communication and are essential for proper brain functioning. In Alzheimer's disease (AD) astrocytes become reactive, which is characterized by an increased expression of intermediate filament proteins and cellular hypertrophy. Reactive astrocytes are found in close association with amyloid‐beta (Aβ) deposits. Synaptic communication and neuronal network function could be directly modulated by reactive astrocytes, potentially contributing to cognitive decline in AD. In this review, we focus on reactive astrocytes as treatment targets in AD in the APPswePS1dE9 AD mouse model, a widely used model to study amyloidosis and gliosis. We first give an overview of the model; that is, how it was generated, which cells express the transgenes, and the effect of its genetic background on Aβ pathology. Subsequently, to determine whether modifying reactive astrocytes in AD could influence pathogenesis and cognition, we review studies using this mouse model in which interventions were directly targeted at reactive astrocytes or had an indirect effect on reactive astrocytes. Overall, studies specifically targeting astrocytes to reduce astrogliosis showed beneficial effects on cognition, which indicates that targeting astrocytes should be included in developing novel therapies for AD. MAIN POINTS: The APPswePS1dE9 mouse displays extensive amyloid‐induced reactive astrogliosis. Reactive astrocytes play a pivotal role in AD pathogenesis as they affect synaptic function. Targeting reactive astrocytes may help to prevent cognitive decline.